THE CONSUMER ACCEPTANCE ON THE “KERNAS” PRODUCED BY USING DIFFERENT COOKING PROCESSES (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThis study aimed to determine the consumer acceptance on thekernasproduced by using different cooking processes. The design used wasnon-factorial completely randomized design (CRD) with 3 kinds of the treatment, namely: fried in oil, coated with banana leaves and then barbequed, and coated with banana leaves then roasted. The results showed that the different cooking process on kernas had significant effects on the organoleptic values of appearance, aroma, taste and texture, as well as the value of water content, fat, protein and total phenols. The deep fried kernaswas the most favored by 65 of 80 panelists (61.25%), characterized by a distinctive brownish color, clearly visible of sago grains (7.7), with a distinctive fish flavor (7.7), had a crunchy-crispy texture butnot hard on the surface but softeninside(7.4), and had afish and savory tasted (7.7). The product was containing 56.14% water, 2.39% ash, 14.48% protein, and 7.09% fat, and containing0.07 ppmtotal phenols.Keywords:browning, kernas, mackarel tuna, sago,